Deliberative Governance Principles in Forest Areas Management with Special Purposes - Kismartini, Kismartini; Warsono, Hardi; Wasiq Hidayat, Jafron; Pujiyono, Bambang; Murtadho Yusuf, Irfan; Nurul Huda, Mohammad (Indonesian Association for Public Administration, 2024)
Apart from having educational and development goals, the management of Diponegoro University's Wanadipa Special Purpose Forest Area (KHDTK) also aims to carry out sustainable forest use activities. The management carries out efforts to achieve these goals through a deliberative governance approach, including public consultation. However, the management is not yet satisfied with the results, considering that the community around the forest has not participated well in managing the KHDTK. Therefore, this research aims to analyze deliberative governance in KHDTK forest management by testing three deliberative governance criteria: representation, participation, and deliberation process. This approach is a collaborative effort between managers of Special Purpose Forest Areas (KHDTK) and farming communities around the forest. Mixed research methods were used in this research, with a concurrent embedded model. The qualitative research approach uses key informants as data sources, while quantitative research uses respondents consisting of forest farmers. The results of the research show that KHDTK forest management based on aspects of representation, participation, and deliberation has not run optimally. Therefore, it is recommended that intensive and open communication between KHDTK managers and forest farming communities be improved in KHDT forest management, which will provide benefits to both parties.